ADP-Ribosylation Factor 6 Regulates Mammalian Myoblast Fusion through Phospholipase D1 and Phosphatidylinositol 4,5-Bisphosphate Signaling Pathways - Bach, Anne-Sophie (The American Society for Cell Biology, 2010)
Myoblast fusion is an essential step during myoblast differentiation that remains poorly understood. M-cadherin–dependent pathways that signal through Rac1 GTPase activation via the Rho-guanine nucleotide exchange factor (GEF) Trio are important for myoblast fusion. The ADP-ribosylation factor (ARF)6 GTPase has been shown to bind to Trio and to regulate Rac1 activity. Moreover, Loner/GEP(100)/BRAG2, a GEF of ARF6, has been involved in mammalian and Drosophila myoblast fusion, but the specific role of ARF6 has been not fully analyzed. Here, we show that ARF6 activity is increased at the time of myoblast fusion and is required for its implementation in mouse C2C12 myoblasts. Specifically, at the onset of myoblast fusion, ARF6 is associated with the multiproteic complex that contains M-cadherin, Trio, and Rac1 and accumulates at sites of myoblast fusion. ARF6 silencing inhibits the association of Trio and Rac1 with M-cadherin. Moreover, we demonstrate that ARF6 regulates myoblast fusion through phospholipase D (PLD) activation and phosphatidylinositol 4,5-bis-phosphate production. Together, these data indicate that ARF6 is a critical regulator of C2C12 myoblast fusion and participates in the regulation of PLD activities that trigger both phospholipids production and actin cytoskeleton reorganization at fusion sites.